ASAL MUASAL DAN PERKEMBANGAN ORDO KETIGA REGULAR FRANSISKUS ASSISI - Antonius Eddy Kristiyanto (P3TK, Sanata Dharma University, 2022)
AbstractThis historical research has focused on the religious movement of the Third Order Regular Francis of Asisi. The followers of the Poor man of Assisi consist of four Franciscan Orders, known today as the Order of Friars Minor, the Order of St. Clare, the Third Order Regular of St. Francis, and the Secular Franciscan Order (formerly known as the Third Order Secular). More than that, the religious vision and Francis’ inspiration are being put into practice by a certain Lutheran denomination and an Anglican church. The research which applied the method of spiritual-historical theology has narrated the emancipatory movements that were realized by the Third Order (penitence) of St. Francis. In fact, there were lay people who would imitate Francis’s way of life within their state of life, in their works, and within their family. This is the origin of Tersiaris (the Secular Franciscan Order). Then, there were some people who would be religious in the spirit of St. Francis by living the holy gospel. In reality, some interventions by the Holy See took part in determining the development of the Third Order Regular of St. Francis, besides the active roles of the members of the First Order (as spiritual fathers) and local bishops. Throughout its long history, the Third Order Regular has served as a kind of sanctity school for its own members as well as those who completely immerse themselves in their service to the world. So, the primary characteristic of the Third Order remains penance, that is the spiritual ideals of Francis of Assisi.AbstrakKajian historis ini menfokuskan perhatian pada gerakan religius Ordo Ketiga Regular Fransiskus Assisi. Para pengikut Si Miskin Assisi terdiri atas empat kelompok, yakni Ordo Pertama (Saudara-saudara Dina), Kedua (Claris), dan Ketiga (Ordo Regular St. Fransiskus), dan Ordo Fransiskan Sekular. Bahkan visi religius dan inspirasi Fransiskus dihayati pula oleh para penganut denominasi Lutheran dan Anglikan. Riset dengan metode teologi historis-spiritual ini menarasikan gerakan emansipatoris yang diwujudkan oleh Ordo Ketiga (Pentobat) Fransiskus. Pada mulanya ada orang-orang awam yang ingin meneladan cara hidup Fransiskus dengan tetap hidup di dunia, dalam pekerjaan sehari-hari dan berkeluarga. Inilah cikal-bakal Tersiaris (Ordo Fransiskan Sekuler). Kemudian ada pula orang-orang yang mau hidup religius dalam prasetia kepada Gereja-Nya dengan semangat Fransiskus, yakni dengan menghayati nasihat-nasihat Injil suci. Dalam praktiknya, selain intervensi-intervensi Takhta Suci ikutserta menentukan perkembangan Ordo Ketiga Regular St. Fransiskus, juga peranan para anggota Ordo Pertama sebagai pendamping rohani, dan ordinaris wilayah. Ordo Ketiga Regular tersebut secara kontinyu menjadi sekolah kesucian bagi para anggota dan mereka yang terlihat sepenuhnya dalam pelayanan pada dunia. Jadi, ciri pembeda utama Ordo Ketiga adalah pertobatan, yang merupakan cita-cita rohani Fransiskus Assisi.